Europe's Disappearing Middle Class? Evidence from the World of Work - Vaughan-Whitehead, Daniel (Edward Elgar Publishing, 2016)
While recent studies have highlighted the phenomenon and risks of increased inequalities between the top and the bottom of society, little research has so far been carried out on trends relating to the median income range that generally represents the middle class. This volume examines the following questions: what are the main transformations in the world of work over the last 20 years in terms of the labour market, social dialogue and conditions of work, wages and incomes that may have affected the middle class? How has the middle class been altered by the financial and economic crisis? What are the long-term trends for the middle class in Europe? This volume also investigates the potential risks and effects of the reshuffling, or even weakening, of the middle class. On the social side, it explores the ramifications of further retrenchment of the European Social Model, which to a great extent has traditionally been funded by the middle class. On the economic side, the book investigates whether this process - especially from the perspective of consumption and human capital - is endangering the long-term sustainability of the current economic model. While presenting evidence of a definite erosion of the middle class, this book assesses the specific situation in each individual EU member state on the basis of detailed statistics and case studies of professional categories that traditionally represent the middle class. This book issues a timely warning about the latest trends and prospects for the middle class in Europe. On this basis, it presents policy considerations and options that will be useful to policy-makers for ensuring the future of the middle class in Europe. Scholars and researchers of European studies and social policy, especially from a sustainability perspective, will find this volume to be an invaluable reference.